Predictors of Parenting: Family-Wide and Child-Specific Factors - Pike, Alison; Atzaba-Poria, Naama; Kretschmer, Tina (Parenting-Science and Practice, 2016)
Objective. The goal of the study was to identify determinants of child perceptions of parenting. Design. By using two children per family, the current study predicted siblings’ (106 pairs) perceptions of mothering and fathering at ages 9–13 from children’s perceptions of parenting and parent ratings of child difficulty, parental emotionality, and household organization, when the children were 4–8 years old. Multi-level modeling was used to differentiate between- and within-family variation. Results. Stability in child perceptions was moderate, and this stability was due to family-wide parenting shared by siblings. Conversely, the majority of variance in the 9- to 13-year-olds’ perceptions indicated differential, rather than similar, parental treatment. Maternal anger predicted maternal hostility. In contrast, household chaos predicted paternal hostility. Conclusions. Relationships between individuals in the family are part of a larger system, and children are equally as likely as parents to reap the benefits of services or interventions directed toward enhancing maternal well-being.
CRIS-Team Scopus Importer:2025-03-19